Thermoelectric thermometry and calorimetry of the active soil layer - Mykytiuk, P.D.; Mykytiuk, O.Yu. (Journal of Thermoelectricity, 2024)
Effective agrotechnical production requires constant monitoring of processes occurring in soils and their thermophysical characteristics, in particular heat fluxes. The existing measurement methods considered are characterized by low accuracy of temperature determination and do not allow determining heat fluxes. This article discusses a patented high-precision thermoelectric agrotester, which allows direct measurement of soil temperature and heat fluxes at the level of 0.01 mW/cm² in the temperature range from - 60 to +150 °C.